Coupled heat and moisture transfer modeling of a PCM–desiccant wall panel for indoor temperature and humidity control: A one-dimensional hygrothermal approach - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Comparative thermo-environ-economic analysis of solar-assisted and conventional ejector-compression heat pump systems for space heating - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Energy and Buildings, 2026)

Geometric optimization of a turbulator in nanofluid flow around a bundle of nuclear reactor fuel rods using the response surface methodology - Jalal Alsarraf; Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed (Annals of Nuclear Energy, 2025)

Sensitivity analysis of parameters and optimization of produced entropy in a nuclear reactor with equilateral fuel rod arrangement and variable angle turbulators - Abdullah A.A.A. Al-Rashed; Abdulwahab A. Alnaqi; Jalal Alsarraf (Annals of Nuclear Energy, 2025)

Numerical investigation of the geometric parameters effect of helical blades installed on horizontal geo heat exchanger - Abdulwahab A. Alnaqi; Abdullah A.A.A. Al-Rashed; Jalal Alsarraf (Geothermics, 2025)

Provenance signature and tectonic setting of the Pliocene Tipam Sandstone Formation from the Chittagong Tripura Fold Belt of the Bengal Basin - Abu Sadat Md. Sayem; Papiya Mondal; Md. Sha Alam; Rashed Abdullah; Julleh Jalalur Rahman; Rumana Yeasmin (Journal of Sedimentary Environments, 2024)

Correction to: Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Ahasanul Hoque (Veterinary Research Communications, 2023)

Mapping of dressed and processed poultry products in Bangladesh: Identifying the food safety risks for policy intervention - Jinnat Ferdous; Md Helal Uddin; Rashed Mahmud; Mathew Hennessey; Abdullah Al Sattar; Suman Das Gupta; Justine S. Gibson; Robyn Alders; Joerg Henning; Guillaume Fournié; Md. Ahasanul Hoque (Veterinary Research Communications, 2023)
Bangladesh’s commercial poultry production is growing rapidly, including the commercial processing of poultry. This expansion of poultry processing plants is fueled by the belief that this sub-sector provides safer food and has less food-borne disease risks compared to traditional live bird markets (LBMs). The purpose of this study is to describe Bangladesh’s dressed and processed poultry production and distribution network (PDN), identify what and where quality control occurs, and suggest where improvements could be made. Engaging with PDN for dressed and processed poultry, we used in-depth interviews with key informants to identify the stakeholders involved and their connections with other poultry PDNs. In addition, we mapped out the supply and distribution of dressed and processed poultry and quality control processes occurring throughout the network. We argue that dressed and processed poultry PDNs are closely connected with traditional PDNs such as LBMs, with multiple crossover points between them. Also, there is a lack of consistency in quality control testing and a lack of meat traceability. Consequently, perceptions of dressed and processed poultry being safer than birds from LBMs needs to be treated with caution. Otherwise, unsubstantiated consumer confidence in dressed poultry may inadvertently increase the risk of food-borne diseases from these products.

Performance of tubular microbial fuel cells using different industrial wastewater - Abdullah Almatouq; Mohd Elmuntasir Ahmed; Mishari Khajah; Hussain Abdullah; Rashed Al-Yaseen; Mariam Al-Jumaa; Farah Al-Ajeel; Ahmed Shishter (Journal of Water Process Engineering, 2023)

Major and trace element geochemistry of the Atrai River sediments from the Bengal Basin (Bangladesh): implication for provenance, chemical weathering, and tectonic setting in the southeastern Himalaya - Abu Sadat Md. Sayem; Md. Rokonuzzaman; Md. Shams Shahriar; Rashed Abdullah; Zahidul Bari; Md. Sazzad Hossen (Arabian Journal of Geosciences, 2023)

The waste heat of a biofuel-powered SOFC for green hydrogen production using thermochemical cycle; Economic, environmental analysis, and tri-criteria optimization - Abdulwahab A. Alnaqi; Jalal Alsarraf; Abdullah A.A.A. Al-Rashed (Fuel, 2023)

A comparative investigation of syngas and biofuel power and hydrogen plant combining nanomaterial-supported solid oxide fuel cell with vanadium-chlorine thermochemical cycle - Abdullah A.A.A. Al-Rashed; Jalal Alsarraf; Abdulwahab A. Alnaqi (Fuel, 2023)

Stock Assessment of Six Sciaenidae Species in the Bay of Bengal, Bangladesh Water Using a Length-Based Bayesian Biomass (LBB) Method - Rokeya Sultana; Qun Liu; Petra Schneider; Md. Abdullah Al-Mamun; Al Mamun; Md. Farhan Tazim; Mohammad Mojibul Hoque Mozumder; Mohammed Rashed Parvej; Md. Mostafa Shamsuzzaman (Fishes, 2022)
Six most abundant and commercially valuable croakers (Sciaenidae) stocks in the coastal water of Bangladesh were evaluated using a length-based Bayesian Biomass (LBB) approach. The ratios B/B0 (current relative biomass) were smaller than the BMSY/B0 in five of the six stocks. For the six estimated populations, two (Otolithes ruber and Pterotolithus maculatus) are grossly overfished, one (Otolithoides pama) is overfished, two (Johnius belangerii and Panna heterolepis) are slightly overfished, and only donkey croaker (Pennahia anea) is in the healthy (B/B0 > BMSY/B0) status. Furthermore, the optimal length at first capture (Lc_opt) was higher than the length at first capture (Lc) in four populations, indicating growth overfishing, suggesting that increasing mesh size would benefit the catch and biomass. Findings from the present study confirm the declining trend of fisheries resources, particularly the croaker species in the BoB, Bangladesh coastal water. Management strategies (such as effort control, choosing the appropriate mesh size, total allowable catch limit, identify and enhance protection of the feeding, breeding, and nursery ground, etc.) should be taken for the sustainable management and recovery of the country’s marine fishing resources, particularly the valuable croaker species.

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

The impact of Rumex vesicarius seed water extracts on mice fertility - Ahmad Rashed Alhimaidi; Aiman Abdullah. Ammari; Mohammad Khair Okla; Muath Qasem Algadi; Ramzi Ahmed Amran; Hissah Ibrahim Alhusayni; Mohammed Ahmad Alhimaidi (Environmental Science and Pollution Research, 2022)
Rumex vesicarius (RV) is an edible wild annual plant, and it is reported that it contains a good source of minerals, protein, and ascorbic acid. Several studies have indicated the anti-liver damage, anticancer, antimicrobial, and antioxidant properties of the RV plant. There are currently no reports regarding the effect of RV on fertility. Therefore, this study focuses on the impact of RV water seed extracts on mice fertility. RV plants were collected, and water seed extracts were prepared; 50 mg/kg body weight (BW) of this was then injected into the mice (male and female) using an oral feeding tube 5 days before mating (group I) or during caging of the females with the males for 1 week to detect their fertility rate. In the different female groups, no significant difference between their BW and their newborn’s BW in the treated and control groups was found. Female fertility, pregnancy, and offspring rates showed some variation within each female group and between the different female groups. In comparing the fertility and offspring rate between the different groups, there was a significant difference ( P < 0.05) between groups I and III females and between groups I and IV females, while the other groups showed no significant differences. In contrast, the other groups showed no significant differences. Regarding the impact of the water seed extract on males, the BW was approximately the same in control and treated males.

Plio-Pleistocene to Recent tectonostratigraphic evolution of the Lalmai anticline in the western Indo-Burman Range (Bangladesh): insights from lithofacies analysis and structural synthesis - Rashed Abdullah; Abu Sadat Md Sayem; Rumana Yeasmin; Mohammad Mashiur Rahman; Zahidul Bari; Farida Khanam (Arabian Journal of Geosciences, 2021)

Sedimentology and basin-fill history of the Cenozoic succession of the Sylhet Trough, Bengal Basin, Bangladesh - Farida Khanam; M. Julleh Jalalur Rahman; M. Mustafa Alam; Rashed Abdullah (International Journal of Earth Sciences, 2021)

Isolation, identification and characterization of endophytic bacteria antagonistic to Phytophthora palmivora causing black pod of cocoa in Malaysia - Wael Alsultan; Ganesan Vadamalai; Ahmad Khairulmazmi; Halimi Mohd Saud; Abdullah M. Al-Sadi; Osamah Rashed; Ahmad Kamil Mohd Jaaffar; Abbas Nasehi (European Journal of Plant Pathology, 2019)

Epidemiological assessment of clinical poultry cases through the government veterinary hospital-based passive surveillance system in Bangladesh: a case study - Md. Ashiqur Rahman; Md. Mahbubur Rahman; Md. Sadeque Abdullah; Md. Abu Sayeed; Md. Harun Rashid; Rashed Mahmud; Joseph P. Belgrad; Md. Ahasanul Hoque (Tropical Animal Health and Production, 2019)

Geotechnical performance of sandy bricks made with fine aggregates of sand dunes, Saudi Arabia - El-Sayed Sedek Abu Seif; Abdullah Rashed Sonbul (Arabian Journal of Geosciences, 2019)

Subcellular Parkinson’s Disease-Specific Alpha-Synuclein Species Show Altered Behavior in Neurodegeneration - Rashed Abdullah; Ketan S. Patil; Benjamin Rosen; Ramavati Pal; Shubhangi Prabhudesai; Sungsu Lee; Indranil Basak; Esthelle Hoedt; Peter Yang; Keith Panick; Hsin-Pin Ho; Emmanuel Chang; et al. (Molecular Neurobiology, 2017)

Adsorptive removal of Cu(II) and Pb(II) onto mixed-waste activated carbon: kinetic, thermodynamic, and competitive studies and application to real wastewater samples - Zeid Abdullah ALOthman; Mohamed Abdelaty Habila; Nora H. Al-Shalan; Sulaiman M. Alfadul; Rahmat Ali; Ibrahim Gar Al alm Rashed; Bader Alfarhan (Arabian Journal of Geosciences, 2016)

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids - Irfan Anjum Badruddin; Salman Ahmed N. J.; Abdullah A. A. A. Al-Rashed; N. Nik-Ghazali; Mohammed Jameel; Sarfaraz Kamangar; H. M. T. Khaleed; T. M. Yunus Khan (Transport in Porous Media, 2015)

Analysis of Heat and Mass Transfer in a Vertical Annular Porous Cylinder Using FEM - Irfan Anjum Badruddin; N. J. Salman Ahmed; Abdullah A. A. A. Al-Rashed; Jeevan Kanesan; Sarfaraz Kamangar; H. M. T. Khaleed (Transport in Porous Media, 2012)